EXPERIMENTAL RESEARCH METHODOLOGY OF FULL-SCALE STEEL AND CONCRETE COMPOSITE CABLE SPACE FRAME PROTOTYPE - Storozhenko, L. I.; Hasii, G. M. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article describes the main features of experimental studies methodology of new space systems constructive solutions effectiveness. Research methodology is developed by the example of full-scale prototype of the steel and concrete composite cable space frame, which consists of space steel and concrete composite modules and flexible bottom chord. Methodology for study stress-strain state of the prototype by testing in the uniform load applied to nodes is developed. It also provides the nodes displacement definition of the prototype. According to the developed technique, stressed state of full-scale prototype of the steel and concrete composite cable space frame was studied with tensionmetric and photogrammetric methods. Equipment and devices arrangement schemes for measuring deformations and displacements of the full-scale steel and concrete composite cable space frames prototype are presented.